Preliminary Studies on the Population Differentiation in Dactyloctenium aegyptium (Linn.) P. Beauv. in Nigeria - Sharma, B. M.; Chivinge, A. O. (Indian Forester, 1983)
Field observations about Dactyloctenium aegyptium (Linn.) P. Beauv. in the University of Ibadan campus in Nigeria revealed important differences among individual plants. The plants were, therefore, classified into three arbitrary groups designated as forms A, B and C. The three forms were subjected to different cultural treatments to find out if the variations justify their designation as ecotypes. The experiments revealed certain persistent differences among the three forms with respect to : (a) growth habit, (b) growth pattern, (c) flowering period, and (d) chromosome numbers. The results indicate that the Nigerian representative species of Dactyloctenium aegyptium is made up of ecotypes.